Pengembangan Media Pembelajaran Interaktif Teknik Dasar Sepak Bola Berbasis Mobile Learning - Eko Bambang Prayoga; Akhmad Sobarna; Ali Budiman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to develop interactive learning media for basic soccer techniques based on mobile learning, and to determine the feasibility, practicality, and effectiveness of the media in Physical Education (PJOK) learning. The study used the Research and Development (R&D) method with the Borg and Gall model. The research subjects consisted of 3 material experts, 3 media experts, 3 PJOK learning experts, 15 students in the small group trial, and 30 students in the large group trial. The research instruments included an expert validation questionnaire, a teacher assessment questionnaire, a student response questionnaire, and a learning outcome test. The results showed that (1) the developed media achieved a very good level of feasibility with an average expert validation score of 91.92%; (2) the practicality test results showed a teacher response rate of 92.50% and a student response rate of 89.33%, categorized as very practical; (3) the effectiveness test results showed a significant increase in student learning outcomes, from an average score of 63.40 in the pretest to 84.27 in the posttest. Thus, the interactive learning media for basic soccer techniques based on mobile learning is declared valid, practical, and effective for use in Physical Education (PJOK) learning. Keywords: Interactive Learning Media, Mobile Learning, Development, PJOK, Basic Soccer Techniques